3(y+4)+6=5(y+6

Simple and best practice solution for 3(y+4)+6=5(y+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(y+4)+6=5(y+6 equation:



3(y+4)+6=5(y+6
We move all terms to the left:
3(y+4)+6-(5(y+6)=0
We multiply parentheses
3y-(5(y+6)+6+12=0

See similar equations:

| -3x=-9-4x^2 | | 7b^2-5=58 | | 3(y+4)+6=5(7y+6) | | x4+2=7 | | 2x+2,1=18,3 | | (x/6)=8-11 | | 7+5(x−3)=22, | | a+7/9=a+5/6 | | 29-n=-4(n-2) | | 7=1+2m-6 | | 5/2x-2=4-3/2x | | .50x+14=30 | | 6(4x+3x)=84 | | 5x=4(3x+6)-3 | | 3(a-6)=-5a-(7+a) | | 7y+15=15 | | (3x+2)*2=81 | | 163=3-4(7n-5) | | 6(x-3)+2x=4(2x+1)-2 | | -18-6x=-4(3x-6) | | 2x+40+90=180 | | 0.1x+5=19-0.5x | | 2/5*m=4/5 | | x+(1/4)=(5/6) | | 170=-5(5m+1) | | 7x/5+3=8 | | 189=-7(-7-4x) | | (1/5)x+5=19-(1/2)x | | 2(4x-5)-2=3x-4 | | 18-4x/0.5=20 | | (3x+2)^2=81 | | 7(r+12)=98 |

Equations solver categories